Recent progress in the development of etomidate analogues - Chen, Yanting; Wu, Lan; Lang, Bingchen; Zhang, Wensheng; Chen, Shouming (Frontiers in Pharmacology, 2025)
Etomidate is a widely utilized anaesthetic agent for the induction of general anesthesia, recognized for its rapid onset and minimal hemodynamic suppression effects. However, its clinical application is constrained by several adverse effects, including adrenal cortex suppression, postoperative nausea and vomiting, and myoclonus. In recent years, there has been a growing global research focus on structural modifications of the etomidate molecule, aiming to simultaneously ameliorate its adverse effects and optimize its hemodynamic stability efficacy. Methoxycarbonyl-etomidate and carboetomidate are inhibited due to the accumulation of their metabolites. CPMM and ET-26HCI have entered the clinical trial stage, but there are still adverse reactions and challenges for the next phase of research. This comprehensive review systematically examines recent scientific advancements in this field, focusing on structural modifications, pharmacological properties, and clinical translation of these novel compounds.